Efficient Regulation of Polysulfides by MoS2/MoO3 Heterostructures for High‐Performance Li‐S Batteries. Issue 16 (22nd January 2023) - Cheng, Pu; Shi, liangliang; Li, Wenqi; Fang, Xiaorong; Cao, Dianliang; Zhao, Yonggang; Cao, Peng; Liu, Dequan; He, Deyan
Abstract: The notorious shuttle effect and sluggish conversion of polysulfides seriously hinder the practical application of Lithium‐sulfur (Li‐S) batteries. In this study, a novel architecture of MoS2 /MoO3 heterostructure uniformly distributed on carbon nanotubes (MoS2 /MoO3 @CNT) is designed and introduced into Li‐S batteries via decorating commercial separator to regulate the redox reactions of polysulfides. Systematic experiments and theoretical calculations showed that the heterostructure not only provides sufficient surface affinity to capture polysulfides and acts as an active catalyst to promote the conversion of polysulfides, but also the highly conductive CNT enables rapid electron/ion migration. As a result, Li‐S batteries with the MoS2 /MoO3 @CNT‐PP separator deliver an impressive reversible capacity (1015 mAh g −1 at 0.2 A g −1 after 100 cycles), excellent rate capacity (873 mAh g −1 at 5 A g −1 ), and low self‐discharge capacity loss (94.6% capacity retention after 7 days of standing). Moreover, even at an elevated temperature of 70 °C, it still exhibits high‐capacity retention (800 mAh g −1 at 1 A g −1 after 100 cycles). Encouragingly, when the sulfur load is increased to 8.7 mg cm −2, the high reversible areal capacity of 6.61 mAh cm −2 can be stably maintained after 100 cycles, indicating a high potential for practical application. Abstract : A novel architecture of MoS2 /MoO3 heterostructure uniformly distributed on carbon nanotubes is designed and introduced into Li‐S batteries to regulate the redox reactions of polysulfides. The heterostructure not only provides sufficient surface affinity to capture polysulfides and acts as an active catalyst to promote the conversion of polysulfides, but also the conductive carbon enables the rapid electron/ion migration.